Specificity of Salt Marsh Diazotrophs for Vegetation Zones and Plant Hosts: Results from a North American marsh - Davis, Debra A.; Lovell, Charles R. (Frontiers in Microbiology, 2012)
Salt marshes located on the east coast of temperate North America are highly productive, typically nitrogen-limited, and support diverse assemblages of nitrogen fixing (diazotrophic) bacteria. The distributions of these diazotrophs are strongly influenced by plant host and abiotic environmental parameters. Crab Haul Creek Basin, North Inlet, SC, USA is a tidally dominated marsh that displays discrete plant zones distributed along an elevation gradient from the tidal creek bank to the terrestrial forest. These zones are defined by gradients of abiotic environmental variables, particularly salinity and sulfide. DGGE fingerprinting and phylogenetic analyses of recovered sequences demonstrated that the distributions of some diazotrophs indicate plant host specificity and that diazotroph assemblages across the marsh gradient are heavily influenced by edaphic conditions. Broadly distributed diazotrophs capable of maintaining populations in all environmental conditions across the gradient are also present in these assemblages. Parsimony test results confirm that diazotroph assemblages in different plant zones are significantly (p<0.01) different across the marsh landscape. Results also indicated that diazotroph assemblages associated with different plant hosts growing in the same area of the marsh were structurally similar confirming the influence of edaphic parameters on these assemblages. Principal Component Analysis of DGGE gel banding patterns confirmed these results. This article reviews and analyzes data from North Inlet Estuary, addressing diazotroph assemblage structure and the influence of plant host and environmental conditions. New data demonstrate the heterogeneity of salt marsh rhizosphere microenvironments, and corroborate previous findings from different plant hosts growing at several locations within this estuary. These data support the hypothesis that the biogeography of microorganisms is non-random and is partially driven by environmental factors.